Reputation: 550
I am attempting to solve a problem of the following kind using dynamic programming - I can't seem to find the recurrence. The problem is as follows :
"A building is a structure formed by a pile of at least two blocks.
Your task is to find total ways, such that all blocks are utilized in making buildings.
For example, for n = 5 the answer is 2 because [5] , [2 , 3] .
For n = 6 the answer is 4 because [6] , [2 , 4] , [2 ,2 ,2] , [3 ,3]"
Can someone help me understand how to do this from a bottom up or top down manner?
Upvotes: 3
Views: 634
Reputation: 23945
There's actually a really simple solution to this: the number of partitions of n
that contain a 1
equals the total number of partitions of (n - 1)
. One way to think of it is imagining removing one 1
from each of the partitions of n
that contain one; any partition of n
that does not contain a 1
cannot be transformed in such a way.
So we can simply remove the first term from the classic partition recurrence, p(k) = p(k − 1) + p(k − 2) − p(k − 5) − p(k − 7) + p(k − 12) + p(k − 15) − p(k − 22) − ...
, and derive:
p_without_1s(k) = p(k − 2) − p(k − 5) − p(k − 7) + p(k − 12) + p(k − 15) − p(k − 22) − ...
Or
p_without_1s(k) = p(k) - p(k - 1)
Upvotes: 0
Reputation: 4356
This has the same idea as the partition problem. Let f[i][j]
detone the number of partitions of i
in blocks of non-decreasing size such that the last block size is j
. Your update rule, then, would be:
f[i+k][k] += f[i][j], for k>= max(2, j) // bottom-up approach
and the answer for the number of partitions:
f[n][2] + f[n][3] + ... + f[n][n]
Alternatively, you could use top-down approach:
f[i][j] += f[i-k][k] for 2 <= k <= j
Running this on your examples you have:
Initialize f[i][i] = 1, i >= 2 and the rest set to 0
f[2][2] = 1
f[3][2] = f[1][2] = 0
f[3][3] = 1
f[4][2] = f[2][2] = 1
f[4][3] = f[1][2] + f[1][3] = 0
f[4][4] = 1
f[5][2] = f[3][2] = 0
f[5][3] = f[2][2] + f[2][3] = 1
f[5][4] = f[1][2] + f[1][3] + f[1][4] = 0
f[5][5] = 1
f[6][2] = f[4][2] = 1
f[6][3] = f[3][2] + f[3][3] = 1
f[6][4] = f[2][2] + f[2][3] + f[2][4] = 1
f[6][5] = f[1][2] + f[1][3] + f[1][4] + f[1][5] = 0
f[6][6] = 1
count(5) = f[5][2] + f[5][3] + f[5][4] + f[5][5] = 2
count(6) = f[6][2] + f[6][3] + f[6][4] + f[6][5] + f[6][6] = 4
Upvotes: 0